(untitled) (Journal of Hama University, 2024)
Abstract A heterocyclic diazo dye containing coumarin structure, which is: 7-hydroxy-4-methyl-8-(4-nitrophenylazo)-6-(4-nitrophenylazo) coumarin, has been synthesized by diazotization a double molar amount of the aromatic amine: 4-nitroaniline. Then coupling reaction of diazonium resulting salt with one molar amount of 7-hydroxy -4- methyl coumarin was done ,the purity of this dye was verified by measuring the melting point and TLC, Purified dye was characterized by spectroscopic methods such as : 1HNMR, IR